Anti MDA-5 associated rapidly progressive interstitial lung disease complicated by viral pneumonia - a fatal outcome - Saikat Mitra; Nithye Parvathy; Mandeep Garg; Shritik Devkota; Sandeep Bansal; Inderpaul Singh Sehgal; Kirti Gupta (University of São Paulo, 2024)
Dermatomyositis is a heterogeneous systemic disease, with 7% to 10% of the individuals presenting the Anti MDA-5 antibody. This subset of patients has clinically amyotropic dermatomyositis, presenting with cutaneous ulcer and rapidly progressive interstitial lung disease. We report the case of a 22-year-old male with a six-month history of low-grade fever associated with myalgia, polyarthralgia, and marked weight loss. He had a history of shortness of breath and high-grade fever 15 days before admission. His clinical features and imaging workup were consistent with acute respiratory distress syndrome. A nasal swab was positive for H1N1 influenza virus infection. During the disease investigation, he succumbed after nine days of admission. The autopsy examination showed diffuse alveolar damage on a background of non-specific interstitial pattern of injury in the lungs. His postmortem muscle biopsy revealed subtle changes of inflammatory myopathy. The brain showed diffuse subarachnoid hemorrhage. Evaluation of postmortem serum sample revealed positivity for Anti MDA-5 and Ro-52 antibodies. This was a case of Anti MDA-5 and Ro-52 associated dermatomyositis with non-specific interstitial pneumonia pattern of lung injury complicated with H1N1 influenza pneumonia, leading to diffuse alveolar damage and subsequent respiratory failure and death. Serum Anti MDA-5 antibodies represent an important biomarker for diagnosing and predicting prognosis for patients with idiopathic inflammatory myopathies, especially clinically amyopathic dermatomyositis. Anti-Ro-52 has been reported in a wide variety of autoimmune diseases, particularly in myositis, scleroderma, and autoimmune liver diseases. Ro-52 autoantibodies are associated with interstitial lung disease (ILD), and their presence should encourage the clinician's curiosity to search for ILD.